Happiness Of Adolescent Social Orphanage Children Tri Murni Padang Panjang - Muhamad Rafi; Netrawati Netrawati (Jurnal Neo Konseling, 2019)
Happiness is a pleasure and tranquility of life inwardly and outwardly achieved through satisfaction of needs and expectations in life. Obtained individual satisfaction is a sign that people are happy. The more people feel satisfied in life, then the individual is the happier.This study aims to (1) Describing happiness teenager at homePure Tri social childcare Padang Panjang based acceptance., (2) describe the happiness teenagers at homePure Tri social childcare Padang Panjang by compassion, (3) describe the happiness teenagers at homePure Tri social childcare Padang Panjang based on merit. This type of research is descriptive quantitative research. The subjects were adolescent social institutions of childcare Tri Murni Leopold. The research subject restricted to the orphanage school teens high school level (high school, vocational and MAN) sebayak 56 people. Research carried out by administering a questionnaire happiness teenage orphanage. Data analyzed using percentages. The research findings indicate the results of happiness (happiness) adolescent social institutions childcare Pure Tri Padang Panjang in the category quite happy. More detailed (1) happiness (happiness) adolescent social institutions asuahan child Tri Murni Padang Panjang on aspects of acceptance is in the category quite happy, (2) happiness (happiness) adolescent social institutions of childcare Tri Murni Padang Panjang on aspects of love that are in category quite happy, (3) happiness (happiness) adolescent social institutions of childcare Tri Murni Padang Panjang on aspects of achievement that are in the happy category. Assistance can be given in this study is in the form of services in guidance and counseling. As for the types of services that can be given in this study were (1) the information service, (2) individual counseling services, (3) placement and distribution, and (4) group counseling services.